2022
DOI: 10.1063/5.0096775
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy of ferroelectrics: The domain wall pinning element

Abstract: We introduce an equivalent-circuit element based on the theory of interface pinning in random systems to analyze the contribution of domain wall motion below the coercive field to the impedance of a ferroelectric, as a function of amplitude [Formula: see text] and frequency [Formula: see text] of an applied ac electric field. We demonstrate our model on a bulk [Formula: see text] (PZT) reference sample and then investigate capacitor stacks, containing ferroelectric [Formula: see text]–[Formula: see text] (BCZT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…30 An addition of frequency dispersion to the Rayleigh element due to the pinning of DW 31 was later provided by Becker et al and applied to epitaxial and polycrystalline ferroelectric 0.5(Ba 0.7 Ca 0.3 )TiO 3 −0.5Ba-(Zr 0.2 Ti 0.8 )O 3 (BCZT) films. 16,17 This study shows an RF-sputtering process for undoped ferroelectric HfO 2 on superconducting NbN electrodes. 32 Such a junction might be an attractive way to develop lowtemperature, low-power superconducting electronics.…”
Section: ■ Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…30 An addition of frequency dispersion to the Rayleigh element due to the pinning of DW 31 was later provided by Becker et al and applied to epitaxial and polycrystalline ferroelectric 0.5(Ba 0.7 Ca 0.3 )TiO 3 −0.5Ba-(Zr 0.2 Ti 0.8 )O 3 (BCZT) films. 16,17 This study shows an RF-sputtering process for undoped ferroelectric HfO 2 on superconducting NbN electrodes. 32 Such a junction might be an attractive way to develop lowtemperature, low-power superconducting electronics.…”
Section: ■ Introductionmentioning
confidence: 93%
“…64 Nevertheless studies by Becker et al have shown a reduction in the coupling factor of frequency dispersion and field dependence for epitaxial ferroelectric BCZT compared to polycrystalline BCZT films. 16,17 This may be explained by the interplay between domain size and grain size of the polycrystalline films. If the grains are smaller than the domains, the film is less responsive to an external electrical field than a system with large grains and small domains.…”
Section: Table 2 Fitting Parameters For Three Different Field Strengt...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we note that there is every reason to believe that also a continous change in resistance (memrisitve behavior) could be achieved in the EFS device by altering the ferroelectric domain structure with subcoercive voltage pulses [40]. The impedance response of memristive EFS devices in intermediated resistance states can be investigated by domain wall pinning element modeling [41], which may help to improve device performance. EFS memristors -acting as artificial synapses -with ultra-low switching voltages may be utilized in the future for direct coupling to a biological neuron, resulting in the formation of a two-terminal neuron-ferroelectric junction.…”
Section: B Device Characterizationmentioning
confidence: 99%